2016
DOI: 10.1097/md.0000000000005425
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of early- and late-onset gout

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 23 publications
2
17
0
Order By: Relevance
“…BMI was one of the variables most significantly associated with the occurrence of metabolic syndrome in HUC29–31 and the percentage of overweight in patients with HUC was increasing 10. Our results also find that patients with early-onset HUC also had a significantly higher BMI (OR 1.281) compared with the healthy people of the same age, which was in accordance with the previous researches 13 19. Obesity could result in an insulin resistant state and compensatory increase in insulin secretion 32.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…BMI was one of the variables most significantly associated with the occurrence of metabolic syndrome in HUC29–31 and the percentage of overweight in patients with HUC was increasing 10. Our results also find that patients with early-onset HUC also had a significantly higher BMI (OR 1.281) compared with the healthy people of the same age, which was in accordance with the previous researches 13 19. Obesity could result in an insulin resistant state and compensatory increase in insulin secretion 32.…”
Section: Discussionsupporting
confidence: 91%
“…Young people are different from the old, they have different lifestyles and hormone levels and the morbidity of complications are lower 16. Some researches tried to describe the pathogenesis and clinical features about early-onset gout and HUC 13 17–19. Yan and her colleagues observed that elevated levels of total cholesterol (TC), triglyceride (TG) and low density lipoprotein (LDL) were independent risk factors for HUC 20.…”
Section: Introductionmentioning
confidence: 99%
“…Recent data suggest that the number of gout patients under the age of 40 years (early-onset) is increasing [ 4 ]. These early-onset patients may have different clinical signs and co-morbidities from those who present with gout at a later age [ 5 , 6 ]. Given the development of earlier metabolic disorders in the early-onset gout patients compared with common gout patients [ 5 ], together with the need for continuous management of health from their younger age, understanding the risks of early-onset gout is clinically important.…”
Section: Introductionmentioning
confidence: 99%
“…One recent study found that patients with early-onset gout were more likely to have polyarticular flares, higher serum uric acid levels, and higher rates of metabolic syndrome [ 8 ]. In a cross-sectional observational study, patients with onset of gout before the age of 40 years had more frequent flares, more joints clinically affected, and fewer cardiovascular, cerebrovascular, and renal comorbidities at presentation but were at higher risk of cardiovascular events [ 9 ]. Furthermore, a stratified analysis conducted as part of a meta-analysis of cohort studies revealed a gradual increase in the risk of myocardial infarction with younger age of gout onset [ 10 ].…”
Section: Introductionmentioning
confidence: 99%